2011
DOI: 10.12693/aphyspola.119.253
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Carbon and Nickel Oxide/Carbon Composites for Supercapacitors

Abstract: In this study a carbon and NiO/carbon electrodes were prepared and investigated. The surface roughness increases with the increase of the torch power. The addition of the NiO changes the surface structure from a snowflake-like to a mesh-like. It was demonstrated that the addition of the nickel oxide to amorphous carbon increases the specific capacitance of composite electrode. However, the NiO/carbon electrodes have a lower breakdown voltage values and longer charge-discharge cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Carbon nanocomposite materials containing metal nanoparticles such as Ni, Co, or Cu or their oxides are appealing for a wide range of applications, including components of scatter radiation absorbent media, heterogeneous catalysts for petrochemical processes, biomedicine, supercapacitor electrode materials and magnetic resonance tomography [107,108]. Metal-carbon nanocomposites with very promising physical, chemical, and mechanical properties are of particular interest to researchers as heterogeneous catalysts for a variety of chemical processes.…”
Section: Nio/carbonous Materials Composites and The Preparationmentioning
confidence: 99%
“…Carbon nanocomposite materials containing metal nanoparticles such as Ni, Co, or Cu or their oxides are appealing for a wide range of applications, including components of scatter radiation absorbent media, heterogeneous catalysts for petrochemical processes, biomedicine, supercapacitor electrode materials and magnetic resonance tomography [107,108]. Metal-carbon nanocomposites with very promising physical, chemical, and mechanical properties are of particular interest to researchers as heterogeneous catalysts for a variety of chemical processes.…”
Section: Nio/carbonous Materials Composites and The Preparationmentioning
confidence: 99%
“…The majority of the authors in this field indicated that these fuels serve as reducing and regulating agents for bio-reduction reactions in the creation of various nanoparticles using the combustion method [1,21]. Contrarily, carbon nanocomposite products containing metal nanoparticles such as copper and cobalt, as well as nickel or its oxides, are an excellent substitute for use in a wide range of applications involving magnetic resonance tomography and biomedicine, electrode materials over super capacitors, heterogeneous catalysts for petrochemical processes, and dispersed radiation-absorbing media [22]. A core/shell structure of Ni-NiO, encapsulated in carbon nanospheres (CNS) and coated with few-and multi-layered graphene (FLG and MLG) was prepared using the chemical vapor deposition (CVD) method [23].…”
Section: Introductionmentioning
confidence: 99%